“Eyrena” is a winter durum wheat variety adapted to the abiotic and biotic factors of environment - N. E. Samofalova; N. P. Ilichkina; O. A. Dubinina; E. V. Ionova; T. S. Makarova; O. A. Kostylenko; A. S. Kameneva; N. S. Kravchenko (Зерновое хозяйство России)
The developed winter durum wheat varieties should combine potential productivity with resistance to abiotic and biotic environmental factors through increased adaptability. The purpose of the study is to evaluate a new winter durum wheat variety “Eyrena” according to its productivity, stress factors resistance and grain quality. The current study of the variety sown after peas, maize for grain, sunflower and in green fallow was performed at the Agricultural Research Center “Donskoy” in 2014–2018. There have been presented morphological, biological, economically valuable traits of the variety “Eyrena” included in the State List of the Breeding Achievements of the Russian Federation in the North Caucasus Region since 2017. The variety is characterized with a high and stable productivity potential. The average productivity over the years of study in the competitive variety testing (2015–2018) ranged according to the forecrops as follows: 8.47 t/ha (green fallow), 6.99 t/ha (peas), 7.29 t/ha (maize for grain), 6.47 t/ha (sunflower). The average increase to the indicators of the standard variety was 0.52; 0.57; 1.41 and 0.75 t/ha, respectively. The maximum productivity (11.80 t/ha) was obtained in the variant with green fallow in 2018. The new variety, in comparison with the standard one, has an increased heat and drought resistance both in the initial phases of plant growth and development and in subsequent periods of active vegetation, has sufficient winter tolerance, and resistance to the main diseases specific for the region. Qualitative traits of grain, groats, pasta comply with the GOST requirements in the country and existing durum wheat standards. The grain hardness on average over the years of study is up to 90% and higher, nature weight is 804 g/l, falling number is 405 sec., protein content in the grain is 3.9%, gluten content is 25.2%, gluten quality (SDS test) is 37 ml, amount of carotenoid is 600 μg/%, pasta color is 4.3 points. The variety “Eyrena”, having a high productivity potential and stability, a number of positive economically valuable traits, can be a good partner to the varieties of this grain crop in the region.